2022
DOI: 10.1177/15385744211068648
|View full text |Cite
|
Sign up to set email alerts
|

SUPERA Stenting in the Common Femoral Artery: Early Experience and Practical Considerations

Abstract: Purpose Endovascular therapy in the management of de novo common femoral disease remains controversial. Considerable interest has been generated in recent years due to recent technological advancement in the design of vascular stents. In particular, SUPERA (Abbot Vascular Inc, Santa Clara USA) stents are designed to offer increased flexibility and less adverse interactions with the arterial wall, thus making it potentially better suited for common femoral lesions. However, despite such theoretical advantages, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…These findings were inconsistent to study conducted by Tao et al, who reported mean PSVR presenting 3.74 AE 7.11 versus 1.12 AE 0.56; however, this difference was not statistically significant (p ¼ 0.11). 5 In the present study, 32 (88.9%) patients reported improvement of the clinical symptoms, 28 (87.5%) patients had intact pulse postoperatively, and 28 (87.5%) had patent vessels. Follow-up showed that none developed reclusion or restenosis during the period of follow-up.…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…These findings were inconsistent to study conducted by Tao et al, who reported mean PSVR presenting 3.74 AE 7.11 versus 1.12 AE 0.56; however, this difference was not statistically significant (p ¼ 0.11). 5 In the present study, 32 (88.9%) patients reported improvement of the clinical symptoms, 28 (87.5%) patients had intact pulse postoperatively, and 28 (87.5%) had patent vessels. Follow-up showed that none developed reclusion or restenosis during the period of follow-up.…”
Section: Discussionsupporting
confidence: 52%
“…These findings were consistent with Toa et al and Gouëffic et al, who reported noninferiority of endovascular tech-nique versus hybrid and open angioplasty techniques in terms of clinical improvement, patency, and intact pulse postoperatively. 5,7 In the current study we did not report any major complications regarding cardiovascular events, cerebrovascular events, stent fracture, 30-day mortality, and morbidity. These findings are better than that reported by several studies investigating the endovascular management of CFA.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations